The influence of video content on TikTok on young people: national identity and cultural communication - Zhanserikova Н.Ж.; Beisenkulov А.А.; Kuantayev Н.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2025)
This article explores the phenomenon of video content distributed through social networks and examines its popularity among contemporary youth. Special attention is devoted to the circulation of national content and the ways in which it is perceived and appropriated by young audiences, highlighting how Kazakh identity is both represented and transformed through digital media practices. The theoretical foundation of the study is the TikTok platform, which in recent years has become one of the most influential environments for the production and consumption of short-form video content. The article analyses existing scholarly perspectives on TikTok and identifies the distinctive patterns of content dissemination among young people. Particular emphasis is placed on the role of digital tools in shaping and reshaping traditional forms of Kazakh worldview within the broader processes of globalization and digitalization. Empirical evidence is provided through statistical data on the digital behaviour of youth in Kazakhstan, further illustrated with concrete examples. The study also examines the phenomenon of aitys (oral improvisational poetry) actively circulating in social media, which reveals the specificity of audiences, feedback mechanisms, and user interaction. Furthermore, the possibility of reproducing identical content across multiple accounts is discussed as a factor that expands reach and alters reception. The article concludes by analysing similarities and divergences in published video materials, the number of views and comments, identifying the main challenges, and proposing possible solutions.